Origin of late Cretaceous phosphorites in Egypt - H Baioumy, R Tada, . (2005)
The Duwi phosphorite deposits in Egypt are a part of the Middle East to North African phosphogenic province of Late Cretaceous–Palaeogene age. Their origin is controversial. Most previous authors have considered them to be in situ, authigenic deposits. Phosphatic grains in the Egyptian phosphorites are well-rounded phosphatic mudclasts (45–65%) and phosphatic bioclasts (35–55%). Phosphatic mudclasts are internally structureless but sometimes contain silt-sized detrital grains such as quartz and bone fragments, suggesting a reworked origin from pre-existing phosphatic mudstone.